Vojtov V.A., Sysenko I.I., Kravtsov A.G. Quality assessment criteria of motor oil for two-stroke internal com-bustion engines. - Войтов, В.А.; Сысенко, И.И.; Кравцов, А.Г. (Problems of Tribology, 2014)
In this paper we propose a dimensionless criterion for the quality of motor oil for two-stroke internal combustion engines. Criterion takes into account antiwear, extreme pressure, anti-friction, antipitting properties and viscosity index oil gasoline indelibly with friction surfaces and the ability to sludging and laking.